Evolution of pyrrolizidine alkaloid biosynthesis in Apocynaceae: revisiting the defence de‐escalation hypothesis - Livshultz, Tatyana (New Phytol, 2018)
Plants produce specialized metabolites for their defence. However, specialist herbivores adapt to these compounds and use them for their own benefit. Plants attacked predominantly by specialists may be under selection to reduce or eliminate production of co‐opted chemicals: the defence de‐escalation hypothesis. We studied the evolution of pyrrolizidine alkaloids (PAs) in Apocynaceae, larval host plants for PA‐adapted butterflies (Danainae, milkweed and clearwing butterflies), to test if the evolutionary pattern is consistent with de‐escalation. We used the first PA biosynthesis specific enzyme (homospermidine synthase, HSS) as tool for reconstructing PA evolution. We found hss orthologues in diverse Apocynaceae species, not all of them known to produce PAs. The phylogenetic analysis showed a monophyletic origin of the putative hss sequences early in the evolution of one Apocynaceae lineage (the APSA clade). We found an hss pseudogene in Asclepias syriaca, a species known to produce cardiac glycosides but no PAs, and four losses of an HSS amino acid motif. APSA clade species are significantly more likely to be Danainae larval host plants than expected if all Apocynaceae species were equally likely to be exploited. Our findings are consistent with PA de‐escalation as an adaptive response to specialist attack.